PENERAPAN STRATEGI SIMULASI PENYUSUNAN OUTLINE PENELITIAN PADA MATA KULIAH METODOLOGI PENELITIAN DI KELAS A1 HUKUM KELUARGA ISLAM - Diyah Setianingsih (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The preparation of a final project is a crucial stage for students in their final semester. In this study, the researcher applied a simulation strategy for developing research outlines in the Research Methodology course. The simulation strategy is an effective model to implement at the beginning of a learning process, as it helps students understand key concepts and principles in organizing a research outline systematically. This study employs a qualitative approach using Classroom Action Research (CAR) with reflective and participatory techniques. The reflective approach ensures that students do not perform the simulation mechanically but instead understand and evaluate the process of constructing a research outline through continuous reflection, enabling them to improve and refine their work progressively. The participatory approach encourages active student involvement as learning subjects, allowing them to discuss, collaborate, and contribute throughout the outline development process. In the context of this simulation strategy, reflective findings show that students of class A1 Islamic Family Law were able to transform their outline-writing experience into meaningful narratives enriched by data triangulation from personal journals and group discussions. Meanwhile, the participatory outcomes indicate enhanced data quality through triangulation of direct observation, informal interviews, and outline preparation, resulting in a comprehensive understanding of the effectiveness of the simulation strategy in building research skills among A1 Islamic Family Law students.